THE PILLARS AND CONDITIONS OF A CONTRACT IN MUAMALAT TRANSACTIONS - Ihsan Helmi Lubis (Institut Agama Islam Negeri Metro, 2023)
Abstract: Buying and selling transactions are natural occurrences that cannot be avoided by every human being because individuals rely on each other for their survival. For example, a meat seller needs a spice seller to enhance the flavor of their cooking, a lecturer needs patients to develop their knowledge, and so on. However, these transactions are inevitably subject to certain conditions and pillars of the contract, which can determine whether the transaction complies with Islamic law or, conversely, contradicts it. The findings of this study reveal that the pillars are divided into four categories, each with its inherent conditions. The first pillar is the presence of two contracting parties with the conditions of legal capacity and multiple parties. The second pillar is the form of the contract with the conditions of clear understanding, matching offer and acceptance, reflecting the sincerity of the parties involved, and taking place in a single gathering. The third pillar is the subject matter of the contract with the conditions that the transaction object must exist at the time of the transaction, be fully owned by its owner, be capable of transfer, have a clear description, and be pure. The fourth pillar is the purpose of the contract with the condition that it must comply with Islamic law.